A time and motion study of subcutaneous versus intravenous trastuzumab in patients with HER2‐positive early breast cancer. (25th January 2016) - De Cock, Erwin; Pivot, Xavier; Hauser, Nik; Verma, Sunil; Kritikou, Persefoni; Millar, Douglas; Knoop, Ann
Abstract : Subcutaneous trastuzumab, delivered via single‐use injection device or handheld syringe, required less patient chair time and active healthcare professional time than intravenous infusion in the PrefHer study. Together with the patient preference for the subcutaneous formulations, our time and motion data support the benefits of transitioning to either subcutaneous delivery method. Abstract: Within PrefHer (NCT01401166), patients and healthcare professionals (HCPs) preferred subcutaneous (SC) over intravenous (IV) trastuzumab. We undertook a prospective, observational time and motion study to quantify patients' time in infusion chairs and active HCP time in PrefHer. Patients with HER2‐positive early breast cancer received four adjuvant cycles of SC trastuzumab (600 mg fixed dose via SC single‐use injection device [SID, Cohort 1] or SC handheld syringe [HHS, Cohort 2]) then four cycles of standard IV trastuzumab or the reverse sequence. Generic case report forms for IV and SC management, both in the treatment room and the drug preparation area, were tailored to reflect center practices. Patient chair time and active HCP time were recorded. We compared pooled Cohort 1 + 2 IV with Cohort 1 SC SID and Cohort 2 SC HHS mean times across eight countries and individually within them utilizing a random intercept generalized linear mixed‐effects model. Per session, the SC SID saved a mean of 57 min of patient chair time versus IV (range across countries: 47–86; P < 0.0001); the SC HHS saved 55 min (40–81; P < 0.0001). Active HCP time was reduced by a mean of 13 min per session with the SC SID (range across countries: 4–16; P < 0.0001) and 17 min with the SC HHS (5–28; P < 0.0001) versus IV. SC trastuzumab, delivered via SID or HHS, saved patient chair and active HCP times versus IV infusion, supporting a transition to either SC method.